ROUTE INTEGRATION OF SEMARANG TRANS FEEDER FOR THE CITY OF SEMARANG AND SURROUNDINGS - Rakhmatulloh, Anita Ratnasari; Dewi, Diah Intan Kusumo; Andini, Titin (Universitas Ibn Khaldun Bogor, 2021)
Inadequate service of Bus Rapid Transit in all zones in an urban area encourages integrated transport management system which can allow transport lines that connect more neighbourhoods which are far from BRT corridor route. Feeder services in Semarang aims at improving accessibility to BRT, reducing traffic congestion caused by the use of private cars and enhancing public transport services in Semarang urban areas and its surrounding. Moreover, Trans Semarang feeder is expected to become a public transport which is representative, safe, convenient, and affordable as well as its lines can be integrated with other transport modes. The purpose of the study is to analyse the integration of feeder route serving more trips in Semarang urban areas and its surrounding by using superimpose analysis and quantitative descriptive analysis. This study reveals that service routes of feeder are not likely to be an optimal, the presence of bus stops amenities has not constituted the minimum requirements of convenience standard, its infrastructure has not integrated yet and the shelter cannot provide easy access to public transport users.